Effects of conventional, diffusion and modern moisture removal methods on quality of stingless bee (Heterotrigona itama Cockerell) honey - Mohd Baroyi, Syahrul Anis Hazwani (2021)
Stingless bee honey produced from Heterotrigona itama is a popular natural sweetener that exhibits numerous bioactivities and health benefits. However, the honey revealed high moisture content (>27.0%), making it highly susceptible to undesirable microbial fermentation. The conventional processing methods practised by the beekeepers in Malaysia were compared, in which the stingless bee honey was subjected to chiller storage (CT), room temperature storage (RT), double-boiled (DB) and open tray drying (OT) for five days. Interestingly, although honey stored at OT was found to reduce a more significant amount of moisture (~38% within five days), the increase of colour intensity and viscosity in OT honey should not be neglected. The colour intensity and viscosity increased from 284 to 314 mm Pfund and 0.13 to 6.80 Pa.s, respectively, in five days, indicating the honey at risk of oxidation and might not reach consumers’ acceptance. Meanwhile, reducing the moisture levels to below 20% without deteriorating honey quality is contemporary urge research. Therefore, this study aimed to evaluate the feasibility of alternative processing methods by utilizing custom-designed clay pots to reduce the moisture content of the stingless bee honey and investigate the physicochemical properties and storage stability of honey. On the other hand, 50 mL of freshly harvested honey were placed in custom-designed clay pots (5 cm diameter x 6 cm height), covered and stored at either 25 ± 1°C (RT) (maintained at 60% relative humidity) or 35 ± 1°C (ET) (maintained at 25% relative humidity). Results showed that the honey's moisture content and water activity after ET storage in clay pots were significantly (p≤0.05) reduced from 25.8% to 19.5% and from 0.79 to 0.70, respectively. Similar degrees of reduction were achieved at RT. However, moisture removal duration took 21 days and resulted in a loss of honey solids (21%) due to cross-wall diffusion. The pH and free acidity of honey were reduced, and the viscosity was increased at the end of storage. Interestingly, hydroxymethylfurfural (HMF) was not detected for all honey, indicating the quality of honey was preserved. The second part of the study was to investigate the effects of modern alternative processing methods, high-pressure processing (HPP) and microwave pasteurization (MW), on the quality of the honey after storage for four weeks. From the results, HPP and MW treatments did not affect the moisture content of the honey compared to the honey without treatment. A similar trend was observed in total soluble solids (TSS), pH, free acidity, colour parameters and viscosity. Meanwhile, the colour intensity increased at the end of storage. The colour intensity of honey without treatment was the highest, followed by MW-treated honey and HPP-treated honey. Sugar profile analysis indicated that all sugar contents were significant reduced after MW and HPP treatments and after four weeks of storage, except the honey treated with HPP at a holding time of 5 minutes. However, neither HPP and MW did prevent the formation of HMF at the end of the storage study. To conclude, it is feasible to use a clay pot to reduce the moisture content in honey where the quality of honey was preserved and HMF formation was avoided. It is also was found to be the most effective method compared to conventional and both thermal and non-thermal alternative methods to increase stingless bee honey storage stability.